PERANCANGAN APLIKASI PEMESANAN MENU MAKANAN DAN MINUMAN PADA CAFE LIVING ROOM BUKITTINGGI BERBASIS VB.NET 2010 - Elma wati; Angga Sahputra (Sekolah Tinggi Teknologi Industri Padang, 2017)
Application of manual work system has several advantages as it did in the café living room. Communication error on the availability of food and beverage menu that makes customer interaction with the waiter became longer because the waiter had to interact with the kitchen, the impact of this incident other customers have to wait when they want to order.To overcome this problem, an application was made ordering food and drink at the cafe living room-based multi-client using vb net in 2010. The use of multi-client choose to reduce the cost of an expensive resource.This design resulted in the application of food and beverage ordering menu-based multi-client that can be installed and run on a computer living room with exe format. With the implementation of this application customer’s can order food menu and choose directly on the customer's computer are provided. Keywords : Multi client, Applications menu reservations